Distributed Networks: New Outlooks on Cerebellar Function - Stella Koutsikou (Frontiers Research Topics, 2015)
Accumulating evidence suggests that the cerebellum subserves functions beyond the sensorimotor realm. This possibility has received considerable attention during the past quarter century, with recent findings revealing putative cerebellar roles in cognition, emotion and spatial navigation. These functions are potentially underpinned by the behaviour-dependent formation of functional networks in which the cerebellum forms one node of distributed circuits spanning thalamic, limbic and neocortical regions. However, these views are not universally accepted. Therefore, the over-arching aim of this Research Topic was to provide a forum through which the debate on the role of cerebellar interactions with motor and "non-motor" structures can be pursued in a rigorous manner. In particular, we aimed to bring together findings from the clinical, animal, theoretical and neuroimaging fields.